PERSEPSI BIDAN TENTANG PENERAPAN ASUHAN KEBIDANAN BERBASIS EVIDENCE-BASED PRACTICE - Rahayu Ningsih; Ricca Nophia Amra (Universitas Methodist Indonesia, 2023)
Evidence-based practice (EBP) in midwifery care is an approach that focuses on using the best scientific evidence for decision making in midwifery practice. It is hoped that the implementation of EBP can improve the quality of midwifery care and improve the health outcomes of mothers and babies. The aim of this research is to explore midwives' perceptions about the implementation of EBP-based midwifery care in Indonesia. Methods This research uses a qualitative design with a phenomenological study approach. Data was collected through in-depth interviews with 10 midwives who work in various practice settings in Indonesia. Data were analyzed using the thematic analysis method. The research results showed that midwives' perceptions regarding the implementation of EBP-based midwifery care varied. Some midwives demonstrated a good understanding of EBP and its benefits in midwifery practice. However, some midwives still have obstacles in implementing EBP, such as lack of access to sources of scientific evidence, time constraints, and a practice culture that does not support EBP. It can be concluded that midwives' perceptions regarding the implementation of EBP-based midwifery care still vary. Efforts are needed to increase midwives' knowledge and skills about EBP, as well as provide easy access to sources of scientific evidence and create a culture of practice that supports EBP.